2017
DOI: 10.3389/fpls.2017.01161
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Histone H3K9 Methylation by BIX-01294 Promotes Stress-Induced Microspore Totipotency and Enhances Embryogenesis Initiation

Abstract: Microspore embryogenesis is a process of cell reprogramming, totipotency acquisition and embryogenesis initiation, induced in vitro by stress treatments and widely used in plant breeding for rapid production of doubled-haploids, but its regulating mechanisms are still largely unknown. Increasing evidence has revealed epigenetic reprogramming during microspore embryogenesis, through DNA methylation, but less is known about the involvement of histone modifications. In this study, we have analyzed the dynamics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 73 publications
3
47
0
Order By: Relevance
“…A recent report has shown that microspore reprogramming and the initiation of embryogenesis are associated with low levels of H3K9 methylation, while embryo differentiation progresses with increasing levels of this histone mark (Berenguer et al, 2017;Rodriguez-Sanz et al, 2014b), as demonstrated by biochemical and H3K9me2 immunofluorescence assays (Fig. 4).…”
Section: Several Reports Have Related Totipotency Of Cells To An Openmentioning
confidence: 71%
See 2 more Smart Citations
“…A recent report has shown that microspore reprogramming and the initiation of embryogenesis are associated with low levels of H3K9 methylation, while embryo differentiation progresses with increasing levels of this histone mark (Berenguer et al, 2017;Rodriguez-Sanz et al, 2014b), as demonstrated by biochemical and H3K9me2 immunofluorescence assays (Fig. 4).…”
Section: Several Reports Have Related Totipotency Of Cells To An Openmentioning
confidence: 71%
“…Interestingly, the temporal profile of bulk H3K9 methylation during microspore embryogenesis correlates with the gene expression patterns of BnHKMT SUVR4-like and BnLSD1-like genes, 'writer' and 'eraser' enzymes of H3K9me2 (Berenguer et al, 2017), providing additional evidence of the developmental regulation of this histone modification during the process of microspore embryogenesis. Moreover, treatment of microspore cultures with the small molecule BIX-01294, a known inhibitor of H3K9 methylation in mammalian cells (Kubicek et al, 2007;Tachibana et al, 2002), promotes microspore reprogramming and embryogenesis initiation, in rapeseed and barley (Berenguer et al, 2017). Conversely, BIX-01294 treatment at advanced stages impairs embryo formation, showing that embryogenesis initiation involves low H3K9 methylation but embryo differentiation requires high levels of this repressive mark.…”
Section: Several Reports Have Related Totipotency Of Cells To An Openmentioning
confidence: 79%
See 1 more Smart Citation
“…3-Methyladenine (3-MA) and MnCl 2 were directly dissolved in the culture medium. Short treatments were carried out from culture initiation during 4 d. Mean percentages of ‘proembryos’ were quantified from random samples of three independent experiments, as previously described ( Berenguer et al , 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…RT-qPCR analyses were performed using the SsoAdvanced™ Universal SYBR ® Green Supermix on the iQ™5 Real-Time PCR Detection Sytem (Biorad). The oligonucleotides used are described in Supplementary Table S2 , and qPCR conditions were as previously described ( Berenguer et al , 2017 ). All qPCRs were run in duplicate, and the Cyclophilin gene was used as the internal reference gene.…”
Section: Methodsmentioning
confidence: 99%